2004
DOI: 10.2337/diacare.27.7.1630
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Social Disengagement in Elderly Diabetic Patients

Abstract: OBJECTIVE -We examined the relationship between health-related social disengagements, as opposed to disengagements related to financial and other non-health-related factors, and subsequent risk of disability and death among initially nondisabled elderly diabetic patients enrolled in Medicare Managed Care plans. RESEARCH DESIGN AND METHODS -We used data from the Medicare HealthOutcomes Survey (HOS) Cohort 1 Baseline (1998) and Cohort 1 Follow-Up (2000). Through mail and telephone surveys, trained interviewers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…One recent study indicated that measures of social functioning were significant predictors of mortality and disability in people with diabetes (14), and the Wisconsin Epidemiologic Study of Diabetic Retinopathy showed that health-related quality of life can predict mortality in people with type 2 diabetes (15). Our study extends these findings by demonstrating that selfreported health profiles can predict which patients are at higher risk for major complications of diabetes even after taking into account established risk factors.…”
Section: Research Design and Methods -The Study Is Based Onsupporting
confidence: 72%
“…One recent study indicated that measures of social functioning were significant predictors of mortality and disability in people with diabetes (14), and the Wisconsin Epidemiologic Study of Diabetic Retinopathy showed that health-related quality of life can predict mortality in people with type 2 diabetes (15). Our study extends these findings by demonstrating that selfreported health profiles can predict which patients are at higher risk for major complications of diabetes even after taking into account established risk factors.…”
Section: Research Design and Methods -The Study Is Based Onsupporting
confidence: 72%
“…Of these, 15 articles met our inclusion criteria and were included in the systematic review. Three of these articles [13], [22], [25] used a different measure of effect size (odds ratio) which cannot be pooled in a meta-analysis with hazard ratios [26]. However, odds ratios can be converted to risk ratios, which then can be combined with hazard ratios in a meta-analysis as forms of relative risks [27].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, health selection may be weaker among late-life immigrants because the decision to migrate is frequently made to join family already living in the United States rather than occupational opportunities ( Angel et al, 2010 ; Gubernskaya, 2015 ). In addition, late-life immigrants may experience disruptions to their long-established social networks, which can potentially lead to social disengagement, loneliness, and decreased social activities; all of which have been associated with poor cognitive and physical functioning ( Barnes-Mauthe, Arita, Allen, Gray, & Leung, 2013 ; Fratiglioni, Wang, Ericsson, Maytan, & Winblad, 2000 ; Holtzman et al, 2004 ; Tsutsumimoto et al, 2017 ; Kuo, Raji, Peek, & Goodwin, 2004 ). For instance, recent research shows higher scores on social frailty (going out less frequently, rarely visiting friends, feeling unhelpful to friends or family, living alone, and not talking with someone every day) are associated with an increased risk of cognitive deficits ( Tsutsumimoto et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%